Implementation of 5S in the Manufacturing Industry - Fitri, Tessa Zulenia; Putra, Rama Dani Eka (Journal of Engineering Science and Technology Management, 2024)
In an increasingly competitive industrial era, reducing waste and increasing operational efficiency has become a primary focus for many organizations. The 5S method, namely Seiri (Sort), Seiton (Arrange), Seiso (Clean), Seiketsu (Standardization), and Shitsuke (Discipline), which originated in Japan and was introduced into the Toyota production system in the 1950s, offers a systematic approach to creating an orderly and clean work environment. This research aims to explore the implementation of 5S at PT XY, with a focus on its impact on operational efficiency and reducing waste in the cement production process. The methodology used in this research includes literature studies and case studies, where data is collected through interviews, direct observation and documentation analysis. The research results show that implementing 5S can increase productivity, create a more organized work environment, and increase employee satisfaction. However, there are several challenges in implementation, especially in the aspects of standardization and discipline among employees. This research also identified problems faced in the project warehouse, such as a lack of personnel, insufficient area, and misunderstandings in shipping goods. Recommendations for improvement include employee training, establishing more comprehensive procedures, and grouping items by type to increase efficiency. Thus, it is hoped that the application of the 5S method at PT XY can create a better work culture and support the sustainability of operational efficiency practices in the future. These findings provide valuable insights for other industries looking to implement 5S to improve their performance and competitiveness.